The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1126/sciadv.abo5633
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the NRF2 transcriptional network as a therapeutic target for trigeminal neuropathic pain

Abstract: Trigeminal neuralgia, historically dubbed the “suicide disease,” is an exceedingly painful neurologic condition characterized by sudden episodes of intense facial pain. Unfortunately, the only U.S. Food and Drug Administration (FDA)–approved medication for trigeminal neuralgia carries substantial side effects, with many patients requiring surgery. Here, we identify the NRF2 transcriptional network as a potential therapeutic target. We report that cerebrospinal fluid from patients with trigeminal neuralgia accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…Furthermore, studies were also conducted to trace the possible upstream signal for the process. Previous studies have reported that 59,60 Nrf2-Keap1 signaling plays an important role in regulating the cellular oxidative stress response, 61,62 and the release of Nrf2 could activate the expression of antioxidant genes (Figure 3F). Therefore, we used Nrf2 siRNA and ML385 inhibitor to knock down or inhibit Nrf2 expression in RBL-2H3 cells to further examine the relationship between the Nrf2-Keap1 signaling pathway and selenoproteins.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, studies were also conducted to trace the possible upstream signal for the process. Previous studies have reported that 59,60 Nrf2-Keap1 signaling plays an important role in regulating the cellular oxidative stress response, 61,62 and the release of Nrf2 could activate the expression of antioxidant genes (Figure 3F). Therefore, we used Nrf2 siRNA and ML385 inhibitor to knock down or inhibit Nrf2 expression in RBL-2H3 cells to further examine the relationship between the Nrf2-Keap1 signaling pathway and selenoproteins.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, oxidative stress was evident in a murine model of TN, and activation of the antioxidant nuclear factor erythroid 2-related factor (2) transcriptional network was shown to have pain-relieving properties through a reduction in oxidative stress. 22…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Nrf2 knockout mice show more severe oxidative stress and neurologic dysfunction after TBI [ 73 ]. Nrf2 also links redox homeostasis to pain perception mechanisms and tolerance [ 74 ].…”
Section: Potential Mechanisms Of Tbi-mediated Increased Risk Of All F...mentioning
confidence: 99%